Pretemporal Transcavernous Approach for Resection of an Orbito-Cavernous Oculomotor Schwannoma - Rutkowski, Martin J. (Journal of Neurological Surgery Part B: Skull Base, 2021)
The following operative video demonstrates surgical tenets and nuances of the pretemporal transcavernous approach in an unusual case of a 33-year-old patient suffering new onset diplopia and a third nerve palsy due to an orbito-cavernous oculomotor schwannoma. Near total resection was accomplished through an extended pterional craniotomy with pretemporal transcavernous exposure of her lesion, resulting in resolution of her preoperative oculomotor palsy and visual dysfunction. When combined with extended pterional and modified frontotemporal orbitozygomatic approaches, the pretemporal transcavernous approach provides excellent surgical access to the parasellar region including the superior orbital fissure and cavernous sinus. Meticulous dissection and early identification of tissue planes, including cranial nerve and vascular anatomy, allows for safe removal of tumors arising in this region.The link to the video can be found at: https://youtu.be/EuIRTP7wWBQ.
Keywords: pterional; oculomotor; schwannoma; cavernous sinus; superior orbital fissure; parasellar; transcavernous